KAJIAN RUANG DAN CAHAYA SEBAGAI TANDA PADA PERISTIWA TEATER REALIS - SHIRLY NATHANIA SUHANJOYO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Realism in theatre brings in reality of life through stage illusion accompanied with signs that can be applicated for eventâ€™s truth attainment. This make the aesthetics of art can be completely felt.Sign in space can be functioned as illustration that brings in act and atmosphere in theatre and it can be explained by arrangement of space and all of its elements. This arrangement is set as one unity such as forms, colors and materials, in order to make those elements support each other in its display. In a realist theatre show,lighting role important; lighting can show object and strengthen act, atmosphere, emotion in order to create act according to concept and further become symbol of script needs. Qualitative and interactive description is applied in order to analyzing space context connected to visual sign system. This system is used in stage, while for the lighting;intensity, color, distribution and movement apply it. Analysis result of space and light as sign explains that human do feel space and its affair into a representation of real life, therefore understanding of script is needed in order to better create the concepts and its imagination.Â Keywords: element; realist; semiotic; stage